2022
DOI: 10.1111/jfpp.16528
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties, oxidative stability, and frying applicability of highly pure soybean‐based diacylglycerol oil

Abstract: As one of the major food components, lipids provide us with energy, essential fatty acids, and lipid-soluble nutrients. However, excessive intake of lipids is known to increase the risk of obesity (Bakir et al., 2014), heart disease (Balk & Lichtenstein, 2017), cancer (Huang et al., 2019), and other health problems (Fulton et al., 2021). Obesity, a metabolic disorder caused by imbalanced energy uptake and expenditure, has become a serious global health problem (Swinburn et al., 2019). In recent years, the mino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
1
3
1
Order By: Relevance
“…Hydrolysis may have also played a role, resulting in the formation of more free fatty acids, as evidenced by the slightly higher FFA content in the fried chicken wings compared with the potato chips. Notably, no significant differences were observed between ED-L and WD-L/WD-P, which is consistent with findings reported by Liu et al [15,23].…”
Section: Peroxide Valuesupporting
confidence: 92%
See 1 more Smart Citation
“…Hydrolysis may have also played a role, resulting in the formation of more free fatty acids, as evidenced by the slightly higher FFA content in the fried chicken wings compared with the potato chips. Notably, no significant differences were observed between ED-L and WD-L/WD-P, which is consistent with findings reported by Liu et al [15,23].…”
Section: Peroxide Valuesupporting
confidence: 92%
“…Li et al suggested that DAG is less stable than TAG and susceptible to the formation of free fatty acids during frying [16]. However, Liu et al found no significant differences in variations of FFA between SBO and SDO during the frying [15]. Our results showed that ED-L with a 1.89% DAG content did not have any significant differences compared to traditionally degummed refined soybean oil [10].…”
Section: Free Fatty Acid Valuecontrasting
confidence: 51%
“…An ultra-performance liquid chromatography (UPLC, Waters, Milford, USA) system equipped with a Acquity UPLC CSH C 18 column (2.1 mm × 50 mm, 1.7 μm, maintained at 60 °C) was coupled online to a quadrupole time of flight mass spectrometry (Q-TOF-MS, Waters, Milford, USA) for glyceride analysis [19] . Eluent A and eluent B were water/acetonitrile (40:60, V/V) and isopropanol/ acetonitrile (90:10, V/V), respectively, both contained 0.1‰ (volume ratio) of formic acid and 10 mmol/L of ammonium acetate.…”
Section: Glyceride Analysis By Uplc-q-tof-msmentioning
confidence: 99%
“…Nowadays, hydrogenated soybean oil and soybean oil catalyzed by enzymatic interesterification ( Wang & Liu, 2014 ), palm olein ( Soo, Tan, Tan, Khalid, & Tan, 2021 ) and rambutan kernel olein ( Wanthong, & Klinkesorn, 2020 ) are used as core material instead of hydrogenated vegetable oil to improve the stability of non-dairy creamer. Our previous study showed that DAGs have higher SFC and melting point compared with TAGs ( Liu et al, 2022 ). Till now, the application of CO-DAG in non-dairy creamer can be hardly found.…”
Section: Introductionmentioning
confidence: 99%